Potensi Maraknya Kasus Dispensasi Nikah Akibat Revisi Undang-Undang Nomor 16 Tahun 2019 tentang Perkawinan di Pengadilan Agama Purwokerto Kelas 1A - Nirmala; Friska Dwi Aryani; Meliana Bernadita; Oktavia Nur Pratiwi (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2024)
Abstract. The marriage age limit is the core of the change in marriage law number 1 of 1974 to law number 16 of 2019. According to the latest law, the minimum age for marriage is equal between men and women, which is 19 years old. However, after the change, the application for marriage dispensation increased at the Purwokerto Religious Court Class 1A. The purpose of this research is to find out the factors that cause the submission of marriage dispensation and the impact it has on the recipients of marriage dispensation. The type of research used in this research is empirical research or field research and uses a qualitative approach. The data used are primary and secondary data. Keywords: Marriage Dispensation, Marriage Law